THE ROLE OF CREATIVE LEADERSHIP IN MANAGING ADMINISTRATIVE TALENT IN THE NATIONAL GYMNASTICS FEDERATION FROM THE POINT OF VIEW OF SCHOLAR - Researchers: Asst. Prof. Dr. Abdul-Hussein Majid Muhammad (Scholars Digest Publishing, 2024)
The study aimed to identify the role of creative leadership in managing administrative talents in the National Gymnastics Sports Federation. The research problem lies in answering the question (what is the role of creative leadership in managing talent administrators in the National Gymnastics Sports Federation) and the researchers used the descriptive approach using the survey method and correlational relationships to form a society The research included (120 ) workers in the National Gymnastics Federation, and the community was divided into the exploratory sample, which numbered (20) workers, and the preparation and application sample (100) workers. Scientific foundations were used in preparing the two scales (creative leadership and management of administrative talents) of validity and reliability, and the data was processed using Statistical Bag for Social Sciences. The researchers concluded that creative leadership works by encouraging and motivating members and providing them with material and moral support, and that the value of administrative talent increases, as the values of creative leadership increase. The researchers recommended that national sports federations should pay attention to holding scientific seminars and discussion groups among members, as this will result in the generation of new innovative ideas. As a result of the diversity of cultures, experiences and knowledge they possess, this in turn contributes to the creation of new working methods, tools and technologies.
Keywords: Creative leadership, administrative talent, National Gymnastics Federation, Sports Management, Employee Motivation.